Fibrous material based on a combination of poly(acrylic acid‐co‐hydroxyethyl methacrylate) with iron ions as a heterogeneous Fenton catalyst for dye oxidative decomposition. Issue 27 (16th March 2017) - Lu, Yuyao; Xu, Naiku; Lv, Yuanyuan; Feng, Yan
ABSTRACT: The Fenton method has been used to remedy dye wastewater because hydroxyl radicals generated from the Fenton reaction can oxidize the dye into small molecules. In comparison with a homogeneous reaction, a heterogeneous reaction with a solid material as a catalyst is a more appropriate alternative for dye wastewater treatment. Because of the large specific surface area and excellent applicability, a novel fibrous material based on a combination of functional polymer with iron ions was designed in this study and used as a heterogeneous catalyst for dye wastewater treatment by the Fenton method. The fibrous material was found to have good catalytic activity for the oxidative decomposition of a variety of dyes and good reusability; additionally, the fibrous material could remove the dye to a greater extent and leave fewer iron ions in the treated wastewater than a homogeneous Fenton catalyst such as iron(II) chloride (FeCl2 ). What is more, the fibrous material could adsorb the residual iron ions from the treated wastewater and make these iron ions take part in the next catalyzation. The previous results make us believe that the prepared fibrous material might be used to create a green approach for dye wastewater treatment. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44875 Abstract :